Obraz Balkánu v českých internetových cestopisech - Šístek, František (Lidé města, 2005)
Internet travellogues are very popular with Czech users of the World Wide Web and their number is constantly growing. Czech internet travellogues dedicated to the Balkans constitute an interesting and yet unexplored source of images of the other, stereotypes and mental maps. The form of travellogues varies from short descriptions of the trip accompanied by several pictures to extensive accounts of the journey, often based on personal diaries. The identity of the authors and participants is sometimes impossible to establish since they frequently use only nicknames and do not provide sufficent personal information. However, it is clear that most authors are young people aged 20–29, often college students or just out of school. Most internet travellogues identify Albania, Bosnia-Hercegovina, Bulgaria, Macedonia, Montenegro, Romania, and Serbia as countries that constitute the region of the Balkans. Greece and Croatia are not regarded as Balkan countries. Instead, they are viewed as typical destinations of Mediterranean summer tourism. The Balkans is much more than a simple geographic term. The terms Balkans (Balkán) and Balkanic (balkánský) as found throughout the analyzed travellogues signify something dangerous, wild, unpredictable, chaotic, absurd and lacking order. These connotations of the term are not necessarily negative – for many young Czech authors of the travellogues, the characterization of the Balkans as a wild and unpredictable place is quite attractive. The Balkans is also associated with images of poverty, negligence, and visible reminders of the Yugoslav wars in the western part of the penninsula. However, signs of modernization and development can be described as Balkanic, too. The encounter with modernization in the supposedly wild and backward region is viewed as something absurd. And absurdity is a notion associated with the Balkans. Generally, any object or situation encountered in the area identified as the Balkans can be labelled as Balkanic. Most travellogues are dedicated to Romania, Bulgaria, and Montenegro. Our travellers are attracted by a combination of wild and relatively unspoiled mountains, historical sights (monasteries, old towns etc.) and Black Sea or Adriatic beaches. Serbia, Bosnia and Macedonia have received only limited attention. These landlocked countries are often closely associated with the images of recent military conflicts. Until recently, the visa regime also made them less attractive than the first three. Albania is definitely viewed as a symbolic heart of the Balkans, a little known, exotic and dangerous land. For many visitors, however, a trip to Albania was a disappointment – the country was too “normal”.